Simulation of the Power Generation Process of a Solid Oxide Fuel Cell Powered by Green Hydrogen from an Alkaline Water Electrolysis - Pedro C. Dias; Alexander Polasek; Jose G. M. Furtado; Alexandre V. Grillo; Roberto B. de Carvalho; Brunno F. dos Santos (Chemical Engineering Transactions, 2025)
Fossil fuels currently meet 80% of global energy demand, significantly contributing to greenhouse gas (GHG) emissions, such as CO2 and CH4. To address this challenge, there is a growing interest in sustainable energy sources with lower environmental impact, such as green hydrogen. This study aims to simulate the performance of a solid oxide fuel cell (SOFC) powered by green hydrogen from alkaline water electrolysis (AEW) and air. Simulations were conducted using Aspen Plus for thermodynamic modeling and Excel for data analysis, exploring different operating temperatures and pressures. Key performance metrics, including polarization curves, power density, and efficiency for the SOFC, and H2 production and voltaic efficiency for the AEW, were evaluated. The results demonstrated optimal conditions at 90 °C and 5 bar for AEW and at 1000 °C and 10 bar for SOFC, achieving an electrical efficiency of 66.63% and a required power input of 9.57 kW for AEW. These findings underscore the feasibility of integrating green hydrogen production and high-efficiency SOFCs for sustainable power generation.